Feasibility and Acceptability of Guided Imagery to Sequentially Address Multiple Health Behaviors During Pregnancy. (12th September 2021) - Giacobbi, Peter; Symons Downs, Danielle; Haggerty, Treah; Pidhorskyi, Stanislav; Long, D. Leann; Clemmer, Melanie; Steinman, Shari A.; Olfert, Melissa D.; Kinnamon, Kelsey; Rao, Neel; Staggs, Hannah; Adjeroh, Donald
Abstract : Introduction: Pregnancy presents health challenges related to well‐being, physical activity, dietary regulation, and body image. There is evidence to support the use of guided imagery to address these concerns during pregnancy. The purpose of this study was to analyze the use and short‐term outcomes of a multiple‐behavior guided imagery intervention delivered through a mobile health (mHealth) application for pregnant women. Methods: A single‐arm, 5‐week feasibility trial was conducted, and participants were instructed to listen to an audio file every day for 35 days on an mHealth application. Measurements included ongoing assessments of the participants' use of the guided imagery audio files and pre‐ and post‐test measures of depression, anxiety, stress, physical activity, food cravings, and body image. Postintervention qualitative interviews were conducted to assess whether participants would continue to use guided imagery. Results: Fifty‐eight participants (mean age, 28.5 years) were enrolled from January to June of 2018. Cloud analytics data showed an average of 4.96 audio downloads per week with the Sleep and Relaxation file being the most widely used (mean weekly usage, 5.67) and reported favorite during follow‐up interviews. Paired‐sample t tests from pre‐ to post‐test showed significant reductions in depression, anxiety, and stress, increased physical activity, and sedentary behavior along with some changes in body image. Discussion: Future scalable guided imagery interventions are justified to test for efficacy. Guided imagery may also be delivered in person by health care providers or by using widely available technologies.